Endoscopic assisted craniotomy for resection of fourth ventricular lesions and confirmation of aqueductal patency via a suboccipital median aperture approach. (October 2020) - Du, Robin; Tafreshi, Ali; Donoho, Daniel; Rutkowski, Martin; Zada, Gabriel
Highlights: Resection of variety of fourth ventricular lesions via median aperture approach. Utility of angled endoscope in suboccipital resection of fourth ventricular lesions. Confirmation of aqueductal patency with endoscope avoids future complications. Abstract: Adequate exposure to fourth ventricular (4V) lesions located adjacent to the cerebral aqueduct and superior medullary velum often mandates extensive telovelar dissection. We assessed the utility of endoscopic assistance via a median aperture approach during suboccipital resection of 4V lesions. We retrospectively reviewed a series of nine patients who underwent suboccipital resection of a 4V lesion via an endoscopic-assisted median aperture approach from 2011 to 2018. Our series included the following pathology: ependymoma (2), rosette-forming glioneuronal tumors (2), pilocytic astrocytoma (1), metastatic melanoma (1), epidermoid cyst (1), organized hematoma (1), and neurocysticercosis (1). Preoperative symptoms included headache (n = 8, 88.9%), nausea (n = 5, 55.6%), vomiting, dizziness, and gait disturbance (n = 4 each, 44.5%). In four cases, the endoscope was used for the majority of the resection or to resect additional tumor located rostrally in the 4V following maximal microscopic resection. In five patients, it was used to confirm extent of resection and patency of the cerebral aqueduct. Gross total resection was achieved in five patients (55.6%). No postoperative complications were attributed to use of the endoscope for additional resection. No patients required immediate CSF diversion, and one patient underwent ventriculoperitoneal (VP) shunt insertion over one year after initial biopsy/fenestration due to tumor progression. Our series is the first to demonstrate the utility of angled endoscopic assistance via a median aperture approach during microsurgical approaches for a variety of 4V lesions. Confirmation of patency of the cerebral aqueduct may help avoid requirements for CSF diversion.